A basic income policy for Peru: can it work? - Cruz-Saco, María Amparo (2002)
This article assesses the pros and cons of a basic income grant and estimates the financial cost of paying a similar benefit to very specific groups in Peru. This is an old concept in the economic literature and is associated with a “negative income tax”. A universal basic income grant can be an adequate instrument to smooth consumption and distribute some purchasing power to the poor. The shift in effective demand after paying a basic income can have important multiplier effects on small local markets and on the creation of work opportunities. The exercise suggests that the implementation of such instrument should be gradual and accompanied by a substantial increase in general government revenues. Since a basic income policy can have a non-trivial positive impact in the reduction of poverty and in increasing both equity and social cohesion, its appropriateness should be given enough thought.